Zearalenone induces intestinal damage and flora disturbance in rats by triggering ferroptosis via the system Xc--GSH-GPX4 signaling pathway - Bingxin Huangfu; Jie Li; Tongxiao Xu; Xinxin Ren; Ruiqi Zhang; Yanan Chen; Jiantang Wang; Kunlun Huang; Xiaoyun He (Ecotoxicology and Environmental Safety, 2025)
Zearalenone (ZEA) is a mycotoxin commonly found in contaminated grains. The colon, a primary site of ZEA exposure, serves as a barrier to prevent its systemic entry. Ferroptosis signaling in intestinal epithelial cells is associated with increased intestinal inflammation. However, the role of ferroptosis in ZEA-induced gut injury is unclear. This study examined the effects of ZEA on ferroptosis signaling in Sprague-Dawley (SD) rats (5 mg/kg body weight, gavage for three weeks) and Caco-2 intestinal epithelial cells (20 μM, 24-hour treatment). ZEA exposure significantly increased intestinal permeability in rats and reduced transepithelial electrical resistance (TEER) in Caco-2 cells. The mRNA expression analysis and protein analyses revealed a marked reduction in tight junction protein expression and increased pro-inflammatory cytokines. ZEA treatment also led to significant iron accumulation in both rat colonic tissue and Caco-2 cells, accompanied by mitochondrial shrinkage and cristae reduction, indicating ferroptosis induction. Further analysis showed that ZEA suppressed system Xc− (SLC7A11 and SLC3A2) expression, reducing glutathione (GSH) levels and down-regulating GPX4, thereby impairing lipid peroxidation clearance. Additionally, ZEA exposure altered gut microbiota composition by decreasing beneficial bacteria and increasing harmful ones, with these microbial changes correlating with ferroptosis markers. In conclusion, ZEA induces colonic ferroptosis by disrupting the system Xc−-GSH-GPX4 axis, and gut microbiota alterations may contribute to this process.